Predictors of unmet needs and psychological distress in adolescent and young adult siblings of people diagnosed with cancer. Issue 3 (17th August 2014) - McDonald, F. E. J.; Patterson, P.; White, K. J.; Butow, P.; Bell, M. L.
Abstract Purpose Predictors of psychological distress and unmet needs amongst adolescents and young adults (AYAs) who have a brother or sister diagnosed with cancer were examined. Methods There were 106 AYAs (12–24 years old) who completed questionnaires covering demographics, psychological distress (Kessler 10), unmet needs (Sibling Cancer Needs Instrument) and family relationships (Family Relationship Index; Adult Sibling Relationship Questionnaire; Sibling Perception Questionnaire (SPQ)). Three models were analysed (demographic variables, cancer‐specific variables and family functioning variables) using multiple linear regression to determine the role of the variables in predicting psychological distress and unmet needs. Results Unmet needs were higher for AYA siblings when treatment was current or a relapse had occurred. Higher scores on the SPQ‐Interpersonal subscale indicating a perceived decrease in the quality of relationships with parents and others were associated with higher levels of distress and unmet needs. The age and gender of the AYA sibling, whether it was their brother or sister who was diagnosed with cancer, the age difference between them, the number of parents living with the AYA sibling, parental birth country, time since diagnosis, Family Relationship Index, Adult Sibling Relationship Questionnaire and the SPQ‐Communication subscale did not significantly impact outcome variables. Conclusions These results highlight the variables that can assist in identifying AYA siblings of cancer patients who are at risk and have a greater need for psychosocial assistance. Variables that may be associated with increased distress and unmet needs are reported to assist with future research. The results are also useful in informing the development of targeted psychosocial support for AYA siblings of cancer patients. Copyright © 2014 John Wiley & Sons, Ltd.